Implementasi Literasi Digital dan Etika Bermedia pada Masyarakat dalam Menghadapi Standar Komunitas Platform Meta dan TikTok - Saud, Jefriyanto (Yayasan Daarul Huda Kruengmane, 2025)
This community service activity was implemented to respond to the challenge of low digital literacy of the Indonesian community amid the rampant use of Meta platforms (Facebook and Instagram) as well as TikTok. Based on We Are Social & Hootsuite’s (2023) report, more than half of Indonesia’s population actively uses social media, however MAFINDO’s (2022) report shows that 60% of hoaks in Indonesia precisely stem from short, illustrated video content. These conditions are exacerbated by the public’s minimal understanding of the community standards enforced by global platforms as well as the limitations of media ethical awareness. These activities were conducted through socialization and Focus Group Discussion (FGD) involving students, college students, and the local community. Main material covers understanding Meta and TikTok community standards, ethical principles of digital communication, as well as national regulations such as Law No. 32 Year 2002 on Broadcasting and P3SPS. Activity results showed there was high participation from the public, an increase in participants’ understanding of media ethics, as well as a change in critical attitudes in curating digital content. These activities also serve to bridge the gap between global community standards and lived local values in Indonesian society. Thus, this dedication program can be a relevant model of public communication ethics-based digital literacy to be applied sustainably in the face of the challenges of the digital space.